2018
DOI: 10.1007/s12070-017-1243-x
|View full text |Cite
|
Sign up to set email alerts
|

Bleomycin Sclerotherapy in Lymphangiomas of Head and Neck: Prospective Study of 8 Cases

Abstract: The aim of this study is to evaluate the role of bleomycin as a primary mode of nonsurgical treatment in lymphangiomas of head and neck and study their complications. This is a prospective study of 8 patients diagnosed with lymphangioma of head and neck presenting to ENT department of Tata main Hospital from December 2014 to January 2017. They were clinically and radiologically evaluated and treated with intralesional injection of bleomycin diluted in normal saline. Complete resolution was seen in 62.5% (5/8) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…The most common drugs used for sclerotherapy are OK‐432 (Picibanil) and bleomycin 35 . Previous studies have shown that the efficacy of OK‐432 and bleomycin in treatment for lymphangiomas is either better than or comparable to that of surgical excision 36–39 . Furthermore, the complication rate of sclerotherapy performed with OK‐432 and bleomycin seems to be lower than that of surgical treatment 11,40 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common drugs used for sclerotherapy are OK‐432 (Picibanil) and bleomycin 35 . Previous studies have shown that the efficacy of OK‐432 and bleomycin in treatment for lymphangiomas is either better than or comparable to that of surgical excision 36–39 . Furthermore, the complication rate of sclerotherapy performed with OK‐432 and bleomycin seems to be lower than that of surgical treatment 11,40 .…”
Section: Discussionmentioning
confidence: 99%
“… 35 Previous studies have shown that the efficacy of OK‐432 and bleomycin in treatment for lymphangiomas is either better than or comparable to that of surgical excision. 36 , 37 , 38 , 39 Furthermore, the complication rate of sclerotherapy performed with OK‐432 and bleomycin seems to be lower than that of surgical treatment. 11 , 40 However, an effective response (shrinkage ≥60%) to sclerotherapy mainly occurs in macrocystic lesions, and the disease recurrence rate is ~9%.…”
Section: Discussionmentioning
confidence: 99%
“…The principles and methods of interventional sclerotherapy [ 17 ] (using bleomycin at the recommended dose of 0.5 mg/kg in an aqueous solution of 1.5 mg/mL) were as follows: (1) to prevent the side effects of sclerosing agents in infants, patients were > 6 months old unless symptoms of oppression occurred; (2) individual cysts had to be > 1 cm in diameter; (3) imaging findings should suggest infiltration of the lesion into adjacent critical structures; (4) Patients with cervical lymphatic malformation and patients complicated by infection first had to undergo anti-inflammatory treatment for 3–5 days before a sclerosing agent will be injected into the lesion; (5) For abscess formation complicating cervical lymphatic malformation, ultrasound-guided puncture and drainage was administered to patients followed by a simultaneous injection of a sclerosing agent; (6) cervical lymphatic malformation patients with haemorrhage first had to undergo haemostasis, after which a sclerosing agent was injected into the lesion; and (7) for patients without complications, a sclerosing agent had to be injected into the lesion or they had to undergo follow-up ultrasonography.…”
Section: Methodsmentioning
confidence: 99%
“…33 The other major complications included abscess in one patient and two patients needing surgical decompression after bleomycin injection for orbital lymphagiomas to improve eyelid position. 39,40 The mean duration of follow-up from the last treatment was 17 months (range -1 month to 7 years). The imaging modality on follow-up was reported only in 817 patients.…”
Section: Outcomementioning
confidence: 99%